Production, Purification And Partial Characterization Of Laccase From The Mushroom Hypsizygus Ulmarius - G. RAVIKUMAR; D. GOMATHI; M. KALAISELVI; C. UMA (International Journal of Pharma and Bio Sciences, 2012)
The aim of the present study reported here is to examine the production, purification and characterization of the enzyme laccase from the mushroom Hypsizygus ulmarius. The culture conditions were optimized for the maximum production of enzymes with different parameters such as incubation time, carbon, nitrogen sources. The enzyme was purified by ammonium sulphate precipitation and partially characterized. The optimum conditions for the maximum production of enzyme were; incubation period 6th day, pH 5.0, temperature 30oC, inoculum 3%, carbon source (xylose 3%) and nitrogen source (KNO3 3%). The enzyme was purified to 5.11 fold with the recovery of 53.33%. The optimum pH and temperature for the purified laccase was found to be 6.0 and 40oC respectively. The enzyme activity was enhanced by the metal ions Mn2+and Cu2+ whereas it was reduced by Fe2+, Na2+ and Co2+. These results suggest that Hypsizygus ulmarius could produce high yield of laccase. With its distinct characteristics laccase could be used for various applications.